Silvopastoral systems in Patagonia, Argentina - Peri, Pablo Luis (2017)
In the late 1800s, agricultural activities in the ‘Pampas’ region near Buenos Aires expanded rapidly, and as a result, livestock production (mainly sheep) was pushed into marginal areas such as Patagonia (Table 11.1). The unknown carrying capacity of Patagonian rangelands resulted in severe overstocking, and this, coupled with the fragility of the environment, the mismanagement of natural resources and other socioeconomic aspects led to a major degradation of the natural resource base. There are more than 6.5 million hectares affected by desertification (del Valle et al., 1995), where annual pasture production does not exceed 40 kg DM ha–1. Furthermore, national and provincial governments began to promote the planting of fast-growing exotic forest species in Patagonia to solve the problem of timber demand and at the same time to diversify the regional production systems using grassland or shrub land sites with different levels of degradation.